ANALISIS SPASIAL UNTUK PEMETAAN POTENSI TAMBAK UDANG DI KELURAHAN SAMBAU DAN BATU BESAR KECAMATAN NONGSA - Arya Afrian Siregar; Farouki Dinda Rassarandi, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Improper utilization of land may result in issues, such as less than optimal land use and possible adverse environmental effects. This research seeks to assess the suitability of land for shrimp farming in the Sambau and Batu Besar sub-districts of Nongsa, Batam City, Riau Islands. The parameters under examination encompass land utilization, soil texture, slope, proximity to the coast, distance from rivers, temperature, water pH, and salinity. This investigation is a descriptive quantitative study focusing on the suitability categories of shrimp pond cultivation areas. It employs the matching method incorporating overlay parameter outcomes. The suitability classes, as determined by this approach, are categorized into four groups: precisely suitable (S1), suitable (S2), conditionally suitable (S3), and unsuitable (N). Spatial analysis findings reveal that the land deemed suitable for shrimp pond cultivation (S2) spans 1.15 hectares (0.02%), whereas conditionally suitable land (S3) encompasses 300.86 hectares (5.17%).